Prediction of Hospitalizations in Systemic Lupus Erythematosus Using the Systemic Lupus International Collaborating Clinics Frailty Index. Issue 4 (17th February 2022) - Legge, Alexandra; Kirkland, Susan; Rockwood, Kenneth; Andreou, Pantelis; Bae, Sang‐Cheol; Gordon, Caroline; Romero‐Diaz, Juanita; Sanchez‐Guerrero, Jorge; Wallace, Daniel J.; Bernatsky, Sasha; Clarke, Ann E.; Merrill, Joan T.; et al.
Abstract : Objective: The Systemic Lupus International Collaborating Clinics (SLICC) frailty index (FI) predicts mortality and damage accrual in systemic lupus erythematosus (SLE), but its association with hospitalizations has not been described. Our objective was to estimate the association of baseline SLICC‐FI values with future hospitalizations in the SLICC inception cohort. Methods: Baseline SLICC‐FI scores were calculated. The number and duration of inpatient hospitalizations during follow‐up were recorded. Negative binomial regression was used to estimate the association between baseline SLICC‐FI values and the rate of hospitalizations per patient‐year of follow‐up. Linear regression was used to estimate the association of baseline SLICC‐FI scores with the proportion of follow‐up time spent in the hospital. Multivariable models were adjusted for relevant baseline characteristics. Results: The 1, 549 patients with SLE eligible for this analysis were mostly female (88.7%), with a mean ± SD age of 35.7 ± 13.3 years and a median disease duration of 1.2 years (interquartile range 0.9–1.5) at baseline. Mean ± SD baseline SLICC‐FI was 0.17 ± 0.08. During mean ± SD follow‐up of 7.2 ± 3.7 years, 614 patients (39.6%) experienced 1, 570 hospitalizations. Higher baseline SLICC‐FI values (per 0.05 increment) were associated with more frequent hospitalizations during follow‐up, with an incidence rate ratio of 1.21 (95% confidence interval [95% CI] 1.13–1.30) after adjustment for baseline age, sex, glucocorticoid use, immunosuppressive use, ethnicity/location, SLE Disease Activity Index 2000 score, SLICC/American College of Rheumatology Damage Index score, and disease duration. Among patients with ≥1 hospitalization, higher baseline SLICC‐FI values predicted a greater proportion of follow‐up time spent hospitalized (relative rate 1.09 [95% CI 1.02–1.16]). Conclusion: The SLICC‐FI predicts future hospitalizations among incident SLE patients, further supporting the SLICC‐FI as a valid health measure in SLE.